USE OF VIDEOLAPAROSCOPY IN ACUTE INTESTINAL OBSTRUCTION (World Bulletin of Public Health, 2023)
Comparative analysis of the results of open and laparoscopic interventions in patients with different forms of acute intestinal obstruction (AIO).
Keywords: Acute intestinal obstruction; adhesion obstruction; treatment; videolaparoscopy